Lossy Point Cloud Geometry Compression via End-to-End Learning - Wang, Jianqiang; Zhu, Hao; Liu, Haojie; Ma, Zhan (IEEE transactions on circuits and systems for video technology, 2021)
This paper presents a novel end-to-end Learned Point Cloud Geometry Compression (a.k.a., Learned-PCGC) system, leveraging stacked Deep Neural Networks (DNN) based Variational AutoEncoder (VAE) to efficiently compress the Point Cloud Geometry (PCG). In this systematic exploration, PCG is first voxelized, and partitioned into non-overlapped 3D cubes, which are then fed into stacked 3D convolutions for compact latent feature and hyperprior generation. Hyperpriors are used to improve the conditional probability modeling of entropy-coded latent features. A Weighted Binary Cross-Entropy (WBCE) loss is applied in training while an adaptive thresholding is used in inference to remove false voxels and reduce the distortion. Objectively, our method exceeds the Geometry-based Point Cloud Compression (G-PCC) algorithm standardized by the Moving Picture Experts Group (MPEG) with a significant performance margin, e.g., at least 60% BD-Rate (Bjöntegaard Delta Rate) savings, using common test datasets, and other public datasets. Subjectively, our method has presented better visual quality with smoother surface reconstruction and appealing details, in comparison to all existing MPEG standard compliant PCC methods. Our method requires about 2.5 MB parameters in total, which is a fairly small size for practical implementation, even on embedded platform. Additional ablation studies analyze a variety of aspects (e.g., thresholding, kernels, etc) to examine the generalization, and application capacity of our Learned-PCGC. We would like to make all materials publicly accessible at https://njuvision.github.io/PCGCv1/ for reproducible research.